Penggunaan Media Domino untuk Meningkatkan Kemampuan Mufrodat Siswa MTSN 2 Kota Malang - Farhan, Amaliah; Umi Mahmudah; Slamet Daroini (Shaut al Arabiyyah, 2023)
The background in this study is the lack of teacher creativity in using media in the learning process at MTsN 2 Malang City. This study aims to determine the mufradat learning process with domino media and to find out the differences in student learning outcomes in mufradat learning using domino media with classes that do not use any media. This research is included in the quantitative research type of experimental research. done by giving pretest and posttest to two classes, namely experimental and control. The object used is class VII D as the control class and VII E as the experimental class. Data analysis was carried out using the independent sample t-test technique. The results obtained showed significant differences between the two classes, namely the experimental and control classes. This is based on the posttest average value of the experimental class 86.61 while the control class 72.15. The results of this analysis indicate that domino media can be used as a solution in improving the mufradat ability of students at MTsN 2 Malang City.